(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
This paper presents a functioning bandpass filter required for the front-end of the UHF RFID receiver since all signals outside the ultra-high frequency (UHF) time-shifting signals backscattered by the transmitter should be filtered. Therefore, taking into cognisance the wide range of link frequencies that the UHF EPC for UHF RFID allows, it is necessary to develop a filter with tight bandwidth to receive the RFID signal. This study addresses the challenge of designing an efficient eighth-order bandpass filter using multiple feedback topology for UHF RFID applications, overcoming limitations of conventional filters in terms of bandwidth control, roll-off rate and gain performance. The EPC standard for UHF RFID permits the communication from the RFID tag to reader in a modulation frequency that ranges from 40 kHz to 640 kHz. The eighth order active R bandpass filter utilizing the multiple feedback was designed by using the multiSim simulation software version 11.1. Comparisons were made between the simulated and constructed filters, Performance metrics were evaluated based on gain, bandwidth, and roll-off rate, comparing simulated and constructed filters to theoretical expectations. Results obtained were compared using filter theory of maximum gain, bandwidth and roll-off rate. The experimental results show a maximum pass-band gain of 118.02 dB, 112.10 dB better than the 109.89dB and 106.50 dB, a roll-off rate of -64.93 dB/decade, 65.549 dB/decade better than the -73.226 dB/decade of the Simulated filter but a bandwidth of 25.10 kHz of the Simulated filter better than the 23.53kHz of the experimental filter, demonstrating improved performance over...